A Manual for Country Economists - Caiola, Marcello (Washington, D.C. : International Monetary Fund, 1995)
This Manual, addressed mainly to new staff members in the area and functional departments of the IMF, presents different ways to tackle specific problems that desk economists encounter in analyzing country data. This guide presents an approach to analyzing financial developments in a country and to evaluating the quality of data at the disposal of the staff.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet